GC-FID Technique for the Quantitative Evaluation of Multiple Residual Organic Solvent Impurities in Fosaprepitant Dimeglumine Drug - Ramakrishna Reddy, H.; Pratap, S.R.; Chandrasekhar, N.; Shamshuddin, S.Z.M. (Asian Journal of Chemistry, 2021)
A proficient and distinct methodology is established for the quantification of multiple residual organic solvent impurities in fosaprepitant dimeglumine drug substance by gas chromatography with headspace sampler (HS-GC) and flame ionization detector (FID). Chromatographic separation was executed on a fused silica dimethylpolysiloxane capillary column (HP-1; USP G2 phase having dimensions, 60 m length × 0.53 mm dia & 5 μm film thickness). The validation of optimized method was carried out in accordance with relevant validation principles. The authenticated procedure was noticed to be specific, precise, linear, accurate, robust and rugged with concentration ranging from lowest quantification level (LQL) to 200% specification level for each residual organic solvent impurities (methanol, ethanol, acetone, isopropyl alcohol, dichloromethane, methyl tert-butyl ether, ethyl acetate, tetrahydrofuran, cyclohexane and toluene). The established technique was productively useful to determine the residual solvent impurities in fosaprepitant dimeglumine.